Desecularizing the Christian Past: Beyond R. A. Markus and the Religious-Secular Divide. By Enrico Beltramini. Amsterdam: Amsterdam University Press, 2023. 244 pp. € 136.00 hardcover - Gregory, Brad S. (Church history, 2024)
Desecularizing the Christian Past: Beyond R. A. Markus and the Religious-Secular Divide. By Enrico Beltramini. Amsterdam: Amsterdam University Press, 2023. 244 pp. € 136.00 hardcover. - Volume 93 Issue 3.